DEVELOPMENT OF INDUSTRY PRACTICE MODEL IN VOCATIONAL HIGH SCHOOL BASED ENTREPRENEURSHIP (Sainteknol : Jurnal Sains dan Teknologi, 2016)
The main objective of this research is to find models of Industry Practice (Prakerin) based entrepreneurship that oriented to the preparation of students and / or vocational school graduates to become entrepreneurs. This Research is designed in two years using the approach to Research and Development (R D). Subjects were two vocational high school (SMK) in Semarang, study program of Mechanical Engineering. Data were collected through interviews, questionnaires, observation, and documentation. Analysis of data through qualitative and quantitative approaches, including the stages of data reduction, data presentation, data verification, and conclusion are carried out simultaneously. While the research results show that the implementation of the Industry Practices (Prakerin) at vocational high school (SMK), both in public or private vocational high school is not specifically designed to prepare students to become entrepreneurs. It is therefore important to develop a Industry Practice Model based entrepreneurship.